Chicago price theory - Jaffe, Sonia P.; Minton, Rob; Mulligan, Casey B.; Murphy, Kevin M. (Princeton University Press, 2019)
Price theory is a powerful analytical toolkit for measuring, explaining, and predicting human behavior in the marketplace. This incisive textbook provides an essential introduction to the subject, offering a diverse array of practical methods that empower students to learn by doing. Based on Economics 301, the legendary PhD course taught at the University of Chicago, the book emphasizes the importance of applying price theory in order to master its concepts. Chicago Price Theory features immersive chapter-length examples such as addictive goods, urban-property pricing, the consequences of prohibition, the value of a statistical life, and occupational choice. It looks at human behavior in the aggregate of an industry, region, or demographic group, but also provides models of individuals when they offer insights about the aggregate. The book explains the surprising answers that price theory can provide to practical questions about taxation, education, the housing market, government subsidies, and much more.